Ninety Minutes to Reduce One's Intention to Eat Meat: A Preliminary Experimental Investigation on the Effect of Watching the Cowspiracy Documentary on Intention to Reduce Meat Consumption - Pabian, Sara; Hudders, Liselot; Poels, Karolien; Stoffelen, Floor; De Backer, Charlotte J. S. (Frontiers in Communication, 2020)
Whereas past research has shown that using environmental arguments to reduce meat intake are unsuccessful in awareness campaigns, popular documentaries might have the potential to successfully change the public awareness of the environmental implications of meat consumption today. This preliminary study aimed to provide first empirical evidence of the potential effects of watching a popular documentary on a less-known environmental topic among a population that are habitual performers of the behavior under discussion. More precisely, the effects of watching “Cowspiracy: The Sustainability Secret” on the awareness of the environmental implications of meat consumption, the attitude towards eating less meat, and the intention to eat less meat in young adults who consume meat on an (almost) daily basis was studied. The potential impact of Cowspiracy was investigated from the Integrated Change Model perspective. Paper-and-pencil questionnaires were administered to N = 47 participants aged between 19 and 32 before and after watching either Cowspiracy (experimental group, n = 26) or Planet Earth (control group, n = 21). Controlling for the influence of predisposing factors (sociodemographic characteristics gender, age, and socioeconomic status), the results show that watching a popular documentary about the environmental impact of meat production (Cowspiracy) can have a significant effect on the awareness of the environmental consequences of meat consumption, the attitude towards eating less meat, and the intention to reduce meat consumption of young (almost) daily meat eaters. However, results should be interpreted with caution, given the preliminary nature of our study.